PENGARUH STATUS KAMPUNG PARIWISATA TERHADAP PERSEPSI KEBAHAGIAAN MASYARAKAT DI KAMPUNG JODIPAN, BLIMBING, KOTA MALANG - Khalid Rahman; Noveria Anggraeni Fiaji; Surya D.E Putra (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2020)
The Influence of Tourism Village Status on Perceptions of Community Happiness in Jodipan, Blimbing, Malang City. The focus of this experiment is the perception of happiness among residents in the Jodipan tourism village. The basic assumption behind this experiment is that changes in the status of slum settlements in the Jodipan village which later turned into a colorful tourist villageof Jodipan are very likely to affect the level of happiness of the people who live there. This study aims to describe (a) the most influential variables in determining the level of happiness in Jodipan Village and (b) whether there is a relationship between the change in status of Kampung Jodipan (from slums to tourism villages) to the perception of happiness of the community. To test these assumptions, this study uses a quantitative-descriptive approach. The data in this study were obtained through questionnaires adjusted for indicators in measuring perceptions of happiness such as: utilization of time and life balance, speech culture and the value of religiosity, physical and mental health, and community solidarity. The data were then validated and analyzed to examine the relationship between independent variables (X), namely the status of tourist village with the dependent variable (Y), which is the perception of happiness. Furthermore, this study also aims to examine the relationship between sub-variable attitudes and sub-variables of perception of happiness as indicators.